EDUQUER AU VIVANT. PERSPECTIVES, RECHERCHES ET PRATIQUES. - MARIE-CLAUDE BERNARD; CATHERINE SIMARD; CORINNE FO (PR DE L'UNIVERSITE LAVAL, 2022)
Regards croisés entre québécois et français, ce manuscrit témoigne de l'urgence de repenser notre rapport au vivant afin de mieux éduquer.
Keywords: Life sciences -- Philosophy.; Life sciences -- Study and teaching -- France.; Life sciences -- Study and teaching -- Qǔbec (Province); Human ecology -- Study and teaching.; Bioethics.; Biology -- Study and teaching.; Education -- Political aspects.; Sciences de la vie -- Philosophie.; Sciences de la vie -- Étude et enseignement -- France.; Écologie humaine -- Étude et enseignement.; Biologie -- Étude et enseignement.; Éducation -- Aspect politique.; EDUCATION / General; Bioethics; Biology -- Study and teaching; Education -- Political aspects; Human ecology -- Study and teaching; Life sciences -- Philosophy; Life sciences -- Study and teaching; France